Subpopulations of illicit drug users reached by targeted street outreach and respondent-driven sampling strategies: implications for research and public health practice. - Rudolph, Abby E; Crawford, Natalie D; Latkin, Carl; Heimer, Robert; Benjamin, Ebele O; Jones, Kandice C; Fuller, Crystal M (Annals of epidemiology, 2011)
To determine whether illicit drug users recruited through respondent-driven sampling (RDS) and targeted street outreach (TSO) differ by comparing two samples recruited concurrently with respect to sample selection and potential recruitment biases.
Keywords: Adolescent; Adult; Community-Institutional Relations; Data Collection; Demography; Drug Users; Female; Humans; Male; New York; Questionnaires; Selection Bias; Substance-Related Disorders; Young Adult